Policing the sex industry: protection, paternalism and politics - Sanders, Teela; Laing, Mary Whowell (Interdisciplinary studies in sex for sale, 2018)
"The exponential growth of sexual commerce, migration and movement of people into the sex industry, as well as localised concerns about transactional sex, are key areas of interest across the urban west. Given the complex regulatory frameworks under-which the sex industry manifests, the role of the police is significant. Policing the Sex Industry draws on the research and expertise of academics and practitioners, presenting advanced scholarship across a range of countries and spaces. Unpicking the relationship between police practice and commercial sex whilst speaking to the current policy agendas, Policing the Sex Industry explores key issues including: trafficking, decriminalisation, localised impacts of punitive policing approaches, uneven policing approaches, hate-crime approaches and the impact of policing on trans sex workers. A dynamic and incisive contribution to existing research, Policing the Sex Industry will appeal to undergraduate and postgraduate students, as well as researchers at all levels, interested in fields including Criminology, Sociology, Gender Politics and Women's Studies"--